Soy biodiesel exhaust is more toxic than mineral diesel exhaust in primary human airway epithelial cells - Landwehr, K.R.; Hillas, J.; Mead-Hunter, Ryan; O'Leary, R.A.; Kicic, Anthony; Mullins, Ben; Larcombe, Alexander (AMER CHEMICAL SOC, 2019)
© 2019 American Chemical Society. As global biodiesel production increases, there are concerns over the potential health impact of exposure to the exhaust, particularly in regard to young children who are at high risk because of their continuing lung development. Using human airway epithelial cells obtained from young children, we compared the effects of exposure to exhaust generated by a diesel engine with Euro V/VI emission controls running on conventional diesel (ultra-low-sulfur mineral diesel, ULSD), soy biodiesel (B100), or a 20% blend of soy biodiesel with diesel (B20). The exhaust output of biodiesel was found to contain significantly more respiratory irritants, including NOx, CO, and CO2, and a larger overall particle mass. Exposure to biodiesel exhaust resulted in significantly greater cell death and a greater release of immune mediators compared to both air controls and ULSD exhaust. These results have concerning implications for potential global health impacts, particularly for the pediatric population.